Essentials of Economics, 9th Edition - N. Gregory Mankiw (Cengage Learning, 2020)
Master the essential principles of economics with the help of today's most popular educational economics series that's trusted worldwide. Mankiw's ESSENTIALS OF ECONOMICS, 9E uses a concise, inviting presentation that emphasizes only the material that helps you better understand the world and economy in which you live. You learn to become a more astute participant in today's economy with a strong understanding of both the potential and limits of economic policy. The latest relevant examples bring economic principles to life. Acclaimed author Gregory Mankiw explains, ""I tried to put myself in the position of someone seeing economics for the first time. My goal is to emphasize the material that learners should and do find interesting about the study of the economy."" Real scenarios, useful economic facts, and clear explanations demonstrate how economic concepts play a role in the decisions you make every day. Important Notice: Media content referenced within the product description or the product text may not be available in the ebook version.